1984
DOI: 10.1037/0022-0663.76.4.647
|View full text |Cite
|
Sign up to set email alerts
|

Television is "easy" and print is "tough": The differential investment of mental effort in learning as a function of perceptions and attributions.

Abstract: The study addressed the question of how learners' a priori perceptions of message categories relate to their perceived self-efficacy in handling them, and how perceptions relate to the amount of invested mental effort (AIME) and learning. The AIME was defined as the number of nonautomatic mental elaborations applied to material and measured by learners' self-reports. It was hypothesized that in the absence of instructions AIME expended in elaborating materials varies as a function of initial perceptions even w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
448
4
18

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 771 publications
(490 citation statements)
references
References 33 publications
20
448
4
18
Order By: Relevance
“…For example, Schunk and colleagues found that perceived self-efficacy for learning correlates positively with students' rate of solution of arithmetic problems (Schunk & Hanson, 1985;Schunk, Hanson, & Cox, 1987). Salomon (1984) has found that self-efficacy is positively related to self-rated mental effort and achievement during students' learning from text material that was perceived as difficult. Regarding the effects of perceived self-efficacy on persistence, path analyses have shown that it influences students' skill acquisition both directly and indirectly by increasing their persistence (Schunk, 1981).…”
Section: Role Of Self-efficacy In Academic Motivationmentioning
confidence: 99%
“…For example, Schunk and colleagues found that perceived self-efficacy for learning correlates positively with students' rate of solution of arithmetic problems (Schunk & Hanson, 1985;Schunk, Hanson, & Cox, 1987). Salomon (1984) has found that self-efficacy is positively related to self-rated mental effort and achievement during students' learning from text material that was perceived as difficult. Regarding the effects of perceived self-efficacy on persistence, path analyses have shown that it influences students' skill acquisition both directly and indirectly by increasing their persistence (Schunk, 1981).…”
Section: Role Of Self-efficacy In Academic Motivationmentioning
confidence: 99%
“…Similarly, perceived competence, which is a related construct that reflects broader perceptions and knowledge (Bong and Skaalvik 2003;Hughes et al 2011;Klassen and Usher 2010), also affects academic motivation and learning outcomes (Bong and Skaalvik 2003;Harter 1990;Ma and Kishor 1997). Moreover, when students' confidence in their own capabilities increases, they tend to use more cognitive and metacognitive strategies irrespective of previous achievement or ability (Pajares 2006) and the willingness to invest mental effort in a task changes as well (Bandura 1977;Salomon 1983Salomon , 1984.…”
Section: Model-observer Similaritymentioning
confidence: 99%
“…However, at very high self-efficacy, some individuals may feel overconfident and reduce their efforts [7], Assuming that individuals feel efficacious about surmounting problems, holding some doubt about whether one will succeed can mobilize effort and lead to better use of strategies than will feeling overly confident [8].…”
Section: Self-efficacymentioning
confidence: 99%